ANALISIS KELAYAKAN BENIH IKAN AIR TAWAR DAN UDANG WINDU DI UPT BALAI BENIH IKAN TANJUNG LAUT INDAH KOTA BONTANG ( Business Feasibility Analysis Of Freshwater Fish And Tiger Shrimp Seeds At UPT. Balai Benih Ikan Tanjung Laut Indah Bontang City ) - SARINAH, SARINAH; GUNAWAN, BAMBANG INDRATNO; PAGORAY, HENNY; ABDUSYSYAHID, SAID; PAMUNGKAS, BAGUS FAJAR; FITRIYANA, FITRIYANA (Universitas Mulawarman (University of Mulawarman), 2023)
The fisheries sector has enormous potential to be developed. One of them is aquaculture. The government in handling this matter established a Fish Seed Center in each region under the auspices of the Directorate General of Aquaculture. Bontang City has a fish seed center located in Tanjung Laut Indah Village. The seeds produced are tilapia, catfish and tiger shrimp. The purpose of this study is to analyze the financial feasibility of commodities in the Fish Seed Center. The sampling method is a case study while the data analysis methods used are Net Present Value, Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period. The research results obtained based on the financial feasibility analysis are NPV (Net Present Value) of Rp. 157,414. 504, IRR (Internal Rate of Return) of 8%, Net Benefit Cost Ratio 1 and Payback Period for 13 years and 4 months. The conclusion obtained in this study is that the cultivation of tilapia, catfish and tiger shrimp seeds at the Fish Seed Center of Bontang City is financially feasible and profitable